Eksperimen Pembelajaran Matematika dengan Strategi Problem Based Learning dan Problem Posing Terhadap Kemampuan Pemecahan Masalah Ditinjau dari Motivasi Belajar Siswa Kelas X Semester Genap di SMK Negeri 2 Sragen Tahun 2015/2016 - Akbar, Fattah Nur, Prof. Dr. Sutama, M.Pd, M. Noor Kholid, S.Pd., M.Pd (2016)
Problem solving is an integral in the learning of mathematics. Problem solving ability is very important for solving the problem is part of the math curriculum, students gain experience possible to use knowledge and skills already possessed. But in reality, the problem solving ability of students have not been as expected. This research three purposes. 1) Analyze and examine the effect of the implementation strategies Problem Based Learning and Problem Posing toward the math problem solving abilities. 2) Analyze and examine the effect of learning motivation toward math problem solving abilities. (3) Analyze and examine interaction between learning strategy with learning motivation towards the math problem solving abilities. The type of the research is quantitative wits quasi-experimental research. The population in this research is all students of X SMK Negeri 2 Sragen of academic year 2015/2016. Sample of this research consisted of two class there are experiment class and control class with the sampling technique that are use is clester random sampling. Methods of data collection use tests and questionnaires. Technique of analyzed used analysis of variance two paths with different cell with a significance level of 5%. Based on the research results: 1) F_A=10,387>F_(0,05;1;56)=4,013 which means that there is an effect of the implementation strategies Problem Based Learning and Problem Posing toward math problem solving abilities. 2) F_B=19,177>F_(0,05;2;56)=3,162 which means that there is an effect of learning motivation toward math problem solving abilities. 3) F_AB=1,467<F_(0,05;2;56)=3,162 which means that there is no interaction between learning strategy with learning motivation towards the math problem solving abilities. Results of the data analysis was obtained: 1) There is an effect of the implementation strategies Problem Based Learning and Problem Posing toward math problem solving abilities. 2) There is an effect of learning motivation toward math problem solving abilities. 3) There is no interaction between learning strategy with learning motivation towards the math problem solving abilities.